2002
DOI: 10.1006/viro.2001.1321
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Immunogenicity of HPV 16 E7 Fusion Proteins in DNA Vaccination

Abstract: DNA vaccination is a promising approach for inducing both humoral and cellular immune responses. For immunotherapy of HPV-16-associated diseases the E7 protein is considered a prime candidate, as it is expressed in all HPV-16-positive tumors. Unfortunately, the E7 protein is a very poor inducer of a cytotoxic T-cell response, when being used as antigen in DNA vaccination. Here we demonstrate that after fusion to protein export/import signals such as the herpes simplex virus ferry protein VP22, E7 can transloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
40
1
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 41 publications
5
40
1
2
Order By: Relevance
“…Our results proved that VP22 could make the SS more easily recognized and processed by the mouse immunity system, and then enhanced the immunogenicity of antigen. Moreover, it is consistent with the results of Michel and Kim (Michel et al, 2002;Kim et al, 2004). They proved that VP22 may improve immune presentation in different ways, either through enhanced direct priming by transfected antigenpresenting cells (APCs) or by amplified cross-presentation after release from transfected nonprofessional APCs.…”
Section: Discussionsupporting
confidence: 89%
“…Our results proved that VP22 could make the SS more easily recognized and processed by the mouse immunity system, and then enhanced the immunogenicity of antigen. Moreover, it is consistent with the results of Michel and Kim (Michel et al, 2002;Kim et al, 2004). They proved that VP22 may improve immune presentation in different ways, either through enhanced direct priming by transfected antigenpresenting cells (APCs) or by amplified cross-presentation after release from transfected nonprofessional APCs.…”
Section: Discussionsupporting
confidence: 89%
“…Although this hypothesis is attractive, several observations indicated that the immune enhancement might be unrelated to the apparent translocatory functions. For example, a VP22 deletion mutant that lacked translocatory activity was, nevertheless, able to increase the immunogenicity of an attached antigen, 28 and VP22 alone appeared to increase tumor immunity, 12 suggesting the possibility that this viral protein might have a nonspecific adjuvant effect.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the CTL tolerance is extremely strong, since attempts to break it with protein or DNA vaccination have thus far been unsuccessful. 12,13 The inability of K10HPV16-E6/E7 Tg mice to mount an E7-specific CTL response is not due to a general CTL unresponsiveness, because these mice are capable of generating specific CTL activity against, for example, ovalbumin. 12 These results suggest that, similar to the HPV-transgenic murine model in which HPV16-E6/E7 is expressed from the K14 promotor, expression from the K10 promotor results in 'split' tolerance, in which antigen-specific CTL responses are strongly suppressed but the antibody and T helper responses remain unaffected.…”
mentioning
confidence: 99%
“…In contrast, pCTL levels in wild-type mice can be determined directly ex vivo, both by Elispot and tetramer analysis. 8 Michel et al 13 recently demonstrated that immunization of K10HPV16-E6/E7 Tg mice with VP22-E7 1-60 DNA was unable to overcome the E7-specific tolerance. Since the experimental conditions of the CTL assay used by these authors differed from the conditions in our experiments, we directly compared the efficacy of the DNA immunization with SFV-enhE6,7 immunization in our model.…”
mentioning
confidence: 99%
See 1 more Smart Citation